Biodegradation of organochlorine compounds with the Pseudomonas chlororaphis strain in liquid medium as the only carbon source - Bautista Bautista, O.; Ortega Sánchez, E.; Tellez Girón, J. D. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2026)
Soils are currently altered due to the presence of pollutants from various sources. Bioremediation is one of the most researched approaches to mitigate the effects of organic waste, especially organochlorine compounds, known for their high resistance to natural biodegradation processes.Strains of the genus Pseudomonas spp. have been widely studied for their ability to survive in environments containing organochlorine compounds and to degrade them. In this study, the Pseudomonas chlororaphis CA-1 strain, isolated from a confinement site containing organochlorine compounds, was used. Growth kinetics were studied in Trypticase soy broth (TSB) and mineral salts medium (MSM) in the presence of the organochlorine substrate (dichlorobenzene 84%, trichlorobenzene 5%, tetrachlorobenzene 10.5%, and pentachlorobenzene 0.5%) as a carbon source. Microbial growth was quantified by optical density and dry weight. The culture was incubated for three days at 30°C, and the characteristic morphology of Pseudomonas was validated using a bacterial smear.The strain was inoculated at two concentrations of the organochlorine substrate as the sole carbon source to evaluate whether its metabolism could assimilate these toxic compounds. The results demonstrate biomass production of 3.49x10-3 µg/mL at 100 ppm, with an organochlorine-substrate removal percentage of 83.6%. At 1000 ppm, a substrate removal percentage of 89.5% was obtained, with biomass production of 1.48x10-3 µg/mL. This demonstrates that P. chlororaphis CA-1 is capable of using organochlorine compounds as a carbon source.
Keywords: Biodegradation, Growth kinetics, Organochlorine substrate, Pseudomonas chlororaphis.